Environmental investigation of 10 cases of nosocomial Bacillus cereus bacteraemia between 2018 and 2023 - Elissa Maalouf; Barthélémy Tosello; Sophie Schipani; Frédérique Gouriet; Claire Nicaise; Alix Lamoureux; Farah Beih; Agnès Delaby; Véronique Roux; Remi N. Charrel; Carole Eldin (Antimicrobial Resistance and Infection Control)
Abstract Background Bacillus cereus can cause severe and potentially fatal bloodstream infections in immunocompromised patients, including preterm neonates. When the infection is nosocomial, investigating a potential environmental source is crucial to mitigate the transmission. This study investigated the potential environmental sources of ten cases of B. cereus bacteraemia in a neonatal intensive care unit. Methods We retrospectively analysed strains from 6 temporal groups of cases involving 10 preterm neonates with bacteraemia (December-2018 to November-2023) and 28 related environmental samples. Strain typing used Multi-locus Sequence Typing (MLST) to identify sequence types (ST), followed by core-genome analysis (cgMLST) and whole genome sequencing (WGS) for strains within the same ST. Results The 10 clinical strains belonged to 10 different STs, while environmental strains fell into 18 STs. Fourteen strains across four STs matched clinical and environmental sources and were grouped into 4 groups (G1 to G4). Two environmental strains linked to clinical cases were isolated from medical offices, and five from nurses’ locker rooms. These strains were analysed by WGS (Illumina) alongside other Bacillus species. G1 and G2 corresponded to B. cereus species whereas strains of G3 and G4 were closely related to B. pacificus and B. paranthracis, respectively. Conclusion We determined that severe B. cereus infections cases in 10 preterm neonates were not linked to each other, but rather to multiple potential environmental reservoirs within the NICU, often located farther from clinical wards than expected. These areas are not subject to same hygienic standards as medical units. Our findings highlight the need for routine monitoring of hand hygiene practices along with close surveillance and systematic biocleaning that targets not only direct patient care areas but also the broader hospital environment.